TAR(p)/ARCH(1) process guaranteed parameter estimation and change-point detection; International MultiConference of Engineers and Computer Scientists, IMECS 2016; Vol. 2 - Burkatovskaya Yu. B. Yuliya Borisovna (2016, 2016)
Title screen